Functional alteration of a dimeric insecticidal lectin to a monomeric antifungal protein correlated to its oligomeric status. - Nilanjana Banerjee (Public Library of Science (PLoS), 2011)
Background Allium sativum leaf agglutinin (ASAL) is a 25-kDa homodimeric, insecticidal, mannose binding lectin whose subunits are assembled by the C-terminal exchange process. An attempt was made to convert dimeric ASAL into a monomeric form to correlate the relevance of quaternary association of subunits and their functional specificity. Using SWISS-MODEL program a stable monomer was designed by altering five amino acid residues near the C-terminus of ASAL. Methodology/principal findings By introduction of 5 site-specific mutations (-DNSNN-), a β turn was incorporated between the 11(th) and 12(th) β strands of subunits of ASAL, resulting in a stable monomeric mutant ASAL (mASAL). mASAL was cloned and subsequently purified from a pMAL-c2X system. CD spectroscopic analysis confirmed the conservation of secondary structure in mASAL. Mannose binding assay confirmed that molecular mannose binds efficiently to both mASAL and ASAL. In contrast to ASAL, the hemagglutination activity of purified mASAL against rabbit erythrocytes was lost. An artificial diet bioassay of Lipaphis erysimi with mASAL displayed an insignificant level of insecticidal activity compared to ASAL. Fascinatingly, mASAL exhibited strong antifungal activity against the pathogenic fungi Fusarium oxysporum, Rhizoctonia solani and Alternaria brassicicola in a disc diffusion assay. A propidium iodide uptake assay suggested that the inhibitory activity of mASAL might be associated with the alteration of the membrane permeability of the fungus. Furthermore, a ligand blot assay of the membrane subproteome of R. solani with mASAL detected a glycoprotein receptor having interaction with mASAL. Conclusions/significance Conversion of ASAL into a stable monomer resulted in antifungal activity. From an evolutionary aspect, these data implied that variable quaternary organization of lectins might be the outcome of defense-related adaptations to diverse situations in plants. Incorporation of mASAL into agronomically-important crops could be an alternative method to protect them from dramatic yield losses from pathogenic fungi in an effective manner.